Oral Administration of Lactobacillus plantarum 299v Reduces Cortisol Levels in Human Saliva during Examination Induced Stress: A Randomized, Double-Blind Controlled Trial - Hannah Andersson; Cecilia Tullberg; Siv Ahrné; Kristina Hamberg; Irini Lazou Ahrén; Göran Molin; Mikael Sonesson; Åsa Håkansson (International Journal of Microbiology)
Objective. To clarify the effect of Lactobacillus plantarum 299v on the salivary cortisol and salivary IgA levels in young adults under examination stress. Design. Forty-one students with an upcoming academic exam were included in a randomized double-blind, placebo-controlled study. The probiotic bacteria or the placebo product was administered in capsules once a day during 14 days. Saliva was collected and a perceived stress test was filled out at each sampling occasion. Saliva was collected for cortisol analysis by Electrochemiluminescence Immunoassay (ECLI) and salivary IgA was analysed by Enzyme-Linked Immunosorbent Assay (ELISA). Abundance of lactobacilli was evaluated by cultivation of saliva on selective medium and identification of L. plantarum 299v was done on randomly selected colonies by a random amplification of polymorphic DNA (RAPD) typing. Results. A significant difference in cortisol levels was found between the treatment group and the placebo group (P<0.05), together with a significant increase in levels of lactobacilli in the treatment group compared with the placebo group (P<0.001). No significant changes were found for salivary IgA. Conclusion. A probiotic bacterium with ability to reduce symptoms of irritable bowel syndrome (IBS) prohibited increased levels of the stress marker cortisol during the examination period. The registration number of the study is NCT02974894, and the study is registered at ClinicalTrials.gov.